Analisis Pengadaan Bahan Pustaka Pada Perpustakaan Universitas Medan Area dalam Memenuhi Kebutuhan Informasi Pemustaka - Surbakti, Khoirunnisa (Prodi Ilmu Perpustakaan dan Informasi Universitas Islam Negeri Raden Fatah Palembang, 2024)
Procurement of library materials is an activity that must be carried out in a library in order to meet the needs of library users. This analysis was carried out at the Medan Area University library. This analysis aims to analyze the implementation of procurement of library material collections in the Medan Area University library. The activity of procuring library material collections aims to ensure that the collections are in accordance with the needs of Medan Area University library users. This research process uses a qualitative approach which refers to non-mathematical data analysis which provides data from direct observation techniques at the Medan Area University library and interviews conducted by Medan Area University library librarians. The results of research at the Medan Area University library show that the factors in procuring library materials are user needs and also the available budget, these two things are the main factors in procuring library materials. Apart from the procurement factor of library materials, the purchase of library material collections is carried out by the Medan Area University library through vendors or third parties, where the third party will purchase the book collections needed by the Medan Area University library. Procurement of library materials at the Medan Area University Library is carried out directly by the librarian at the library.